2013
DOI: 10.1039/c3nr02678g
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy induced band gap narrowing of ZnO nanostructures by an electrochemically active biofilm

Abstract: Band gap narrowing is important and advantageous for potential visible light photocatalytic applications involving metal oxide nanostructures. This paper reports a simple biogenic approach for the promotion of oxygen vacancies in pure zinc oxide (p-ZnO) nanostructures using an electrochemically active biofilm (EAB), which is different from traditional techniques for narrowing the band gap of nanomaterials. The novel protocol improved the visible photocatalytic activity of modified ZnO (m-ZnO) nanostructures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
324
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(343 citation statements)
references
References 53 publications
18
324
1
Order By: Relevance
“…[53][54][55] Due to the fact that TiO 2 and ZnO possess typical oxygen related defects, the defect sites are subjected to the chemisorption of the above ions while sharing the lattice electron(s). [53][54][55] Furthermore, the grain boundaries (as seen in the TEM images) are obvious locations for electron decient species to chemisorb. Depending on the availability of free electron(s), the sharing can be partial with the above species which has produced relatively broad binding energies peaking at $532.2 eV or $531.9 eV.…”
Section: Photocatalytic Activity Of Core-shell Heterojunction Nanobersmentioning
confidence: 99%
“…[53][54][55] Due to the fact that TiO 2 and ZnO possess typical oxygen related defects, the defect sites are subjected to the chemisorption of the above ions while sharing the lattice electron(s). [53][54][55] Furthermore, the grain boundaries (as seen in the TEM images) are obvious locations for electron decient species to chemisorb. Depending on the availability of free electron(s), the sharing can be partial with the above species which has produced relatively broad binding energies peaking at $532.2 eV or $531.9 eV.…”
Section: Photocatalytic Activity Of Core-shell Heterojunction Nanobersmentioning
confidence: 99%
“…However, the band gap energy variations seen could be caused by defects, crystal structure, and temperature of MO nanoparticles. 41,42 Photoexcitation responses can also be confirmed using UV and Fourier transforminfrared spectroscopy (FT-IR). 43 The dual UV-MO nanoparticle hybrid system can be applied for the disinfection of bacteria and viruses.…”
mentioning
confidence: 99%
“…A previous study reporting the synthesis of graphene-hybridized ZnO triangles attributed its increased output photocurrent density of 1.26 mA·cm −2 (compared to 0.321 mA·cm −2 ) to an increase of oxygen defects in the ZnO triangle nanostructure [68]. Other studies have indicated that the presence of oxygen vacancies narrows the band gap of ZnO [69,70], leading to reduced overpotential for photoexcitation of electrons. Thus, the light absorption properties of ZnO is tunable by controlling the intrinsic defect states [71].…”
Section: Modifications Of Zno For Enhanced Photocatalytic Water Oxidamentioning
confidence: 99%